Introduction to the "Dialogues concerning natural religion" of David Hume - McEwen, Bruce (The University of Edinburgh, 1906)
In professing to call attention to this often forgotten work of the great Scottish Philosopher one can- not help noticing how very similar the reception accorded to it by the outside world has been to its treatment at the hands of the author himself. During his lifetime he kept it in the safe obscurity of his study drawer, where it lay until the day of his death. The plan of the Dialogues had been clearly thought out by Hume as early as 1750 and the active period of his contribution to philosophy proper having closed almost in the same year this excursion of his into natural theology might most fitly have been presented to his readers at once, especially if, as it seems to us now, it may he rightly regarded as the crown and consummation of his earlier speculations. indeed some such conception of the relation of the Dialogues to his other works underlies the outlining of his scheme upon its first page, where he founds his method "on the saying of" an ancient (Chrysippus) that students of philosophy ought first to learn Logics, then Ethics, next Physics, "last of all the nature of the Gods."
An introduction to the "Dialogues concerning natural religion" of David Hume